2014
DOI: 10.1682/jrrd.2013.06.0150
|View full text |Cite
|
Sign up to set email alerts
|

Posture-dependent control of stimulation in standing neuroprosthesis: Simulation feasibility study

Abstract: Abstract-We used a three-dimensional biomechanical model of human standing to test the feasibility of feed-forward control systems that vary stimulation to paralyzed muscles based on the user's posture and desire to effect a postural change. The controllers examined were (1) constant baseline stimulation, which represented muscle activation required to maintain erect standing, and (2) posture follower, which varied muscle activation as a function of the location of the projection of whole-body center of mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Simulation studies have suggested that effective posture shifting [Audu, Nataraj et al 49] and maintenance [Nataraj, Audu et al 50] at leaning postures are feasible with stimulation of muscles that produce lower forces as typical following paralysis. In simulation, it has also been shown that a presumed user-driven system to initiate shifting with their upper-body to leaning postures can also be developed [Audu, Gartman et al 51]. Specifically, a controller that modulates activation levels of target paralyzed muscles according to the neuroprosthesis user driving total body center of mass to a desired location reduces the effort the user may exert to do so when compared to constant activation of those muscles.…”
Section: - Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation studies have suggested that effective posture shifting [Audu, Nataraj et al 49] and maintenance [Nataraj, Audu et al 50] at leaning postures are feasible with stimulation of muscles that produce lower forces as typical following paralysis. In simulation, it has also been shown that a presumed user-driven system to initiate shifting with their upper-body to leaning postures can also be developed [Audu, Gartman et al 51]. Specifically, a controller that modulates activation levels of target paralyzed muscles according to the neuroprosthesis user driving total body center of mass to a desired location reduces the effort the user may exert to do so when compared to constant activation of those muscles.…”
Section: - Overviewmentioning
confidence: 99%
“…Utilizing a three-dimensional model of standing (FIGURE 3) that includes the lower-extremities [Zhao, Kirsch et al 87] and trunk [Lambrecht, Audu et al 88, Wilkenfeld, Audu et al 89], and then adjusted for the passive joint properties and moment generating capacities with stimulation after SCI [Nataraj, Audu et al 47], FNS feedback control systems for postural balance have been created and initially evaluated in simulation [Nataraj, Audu et al 20, Nataraj, Audu et al 43, Audu, Nataraj et al 49, Nataraj, Audu et al 50, Audu, Gartman et al 51, Nataraj, Audu et al 74]. Our group has observed that FNS standing users under external perturbations with walker support demonstrate minimal changes in posture including the arms such that the support loads at the hands can be effectively assumed to be equivalently applied at the shoulder joints to the torso [Nataraj, Audu et al 22, Nataraj 42, Nataraj, Audu et al 47].…”
Section: - Previous Studiesmentioning
confidence: 99%
“…For the trunk, three additional DOFs were defined for a single joint at the lumbosacral transition (L5-S1). The muscle groups under active control were consistent with those targeted by an existing 16-channel implanted system [17] and identified as beneficial for transitioning to leaning postures [18]. This maximum muscle force parameters were scaled to reflect the effects of SCI according to procedures outlined in [5].…”
Section: Methodsmentioning
confidence: 98%
“…First, an optimization routine described in [18] solves for the joint angles for each posture CoM-Pos with coordinates in the anterior-posterior (AP) and medial-lateral (ML) dimensions serving as the optimization constraints. Nine rows of postures were equally spaced along each dimension, yielding a total of 81 test postures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation